CORPORATE GOVERNANCE DAN PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP AGRESIVITAS PAJAK - Latifah Ayu Adharani; Junaidi Junaidi (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2022)
The purpose of this study is to determine the effect of corporate governance and disclosure of corporate social responsibility (CSR) on tax aggressiveness. Corporate governance is proxied by the size of the board of directors, the proportion of independent commissioners, the expertise of the audit committee, and public ownership. For disclosure of corporate social responsibility based on disclosure sustainability report with GRI G.4 Standards and for tax, aggressiveness is proxied by the effective taxes rates. This study takes the research object of companies listed in the Indonesia Stock Exchange in the financial and non-financial sectors of the 2015-2019 period with a total sample of 85 samples and the analysis technique used is multiple regression analysis. The results of this study indicate that: (1) the size of the board of directors harms tax aggressiveness, (2) the proportion of independent commissioners has a positive effect on tax aggressiveness, (3) expertise of audit committee members has no effect on tax aggressiveness, (4) public ownership has no effect on tax aggressiveness, (5) disclosure of corporate social responsibility has no effect on tax aggressiveness.